'Gooin t' schoo': The Subject of Adult Education in Dialect Poetry from the Lancashire Cotton Famine 1861–65. - Rennie, Simon (19: Interdisciplinary Studies in the Long Nineteenth Century, 2025)
'The Beddin's Goan', published in the Blackburn Times in November 1862 by W. A. Abram, begins with the lines 'EH! Robbut! th' lan'lord's bin tu-day, | Whol tha wor deawn at th'class', encapsulating links between unemployment, poverty, and education which became apparent to industrial workers during the Lancashire Cotton Famine. Examining poems from the Cotton Famine poetry database, this article considers how adult education and cultures of literacy are addressed in dialect poetry during the crisis. It finds that, in contrast to standard English poetry on the subject, dialect poetry displays inherent irony in its linguistic tensions, and is often more explicitly class conscious and socially resistant. Aspects of double address allow for more complex commentaries on programmes of social improvement, as do the greater variety of poetic voices. Dialect poems discussed address advances in education and literacy precipitated by measures to counter social degradation during the crisis, but which contributed to the suppression of distinctive working-class cultures. As a self-conscious literary form reliant on the perception of working-class authenticity, dialect poetry of the Cotton Famine offers examples of decay and resistance which represent an intriguing window into a little studied but historically significant period of working-class British culture.